A calculation method for the mode II fracture energy release rate of dissimilar materials adhesively bonded structures. Issue 5 (23rd January 2023) - Wang, Jian; Ding, Huiming; Jiang, Junxia; Bi, Yunbo
Abstract: Nowadays, fracture characterization of dissimilar materials adhesively bonded structures still generally refers to standards for fiber‐reinforced plastic composites. Moreover, the calculation methods of fracture energy release rate specified in these standards often lead to great deviation due to the differences in material properties and geometry. In this paper, dissimilar materials corrected beam theory with effective crack length (DM‐CBTE) method for calculation of mode II fracture energy release rate of dissimilar materials adhesively bonded structures was proposed. The differences in material properties and geometry as well as the effect of clamp were all considered. The experimental and J‐integral numerical analysis results showed that the maximum deviation of the G IIC calculated by the methods recommended in standard from the J‐integral result is 28% while that by the DM‐CBTE method is only 5%, which proved good feasibility of the DM‐CBTE method for evaluation of mode II fracture performance of dissimilar materials adhesively bonded structures. Highlights: DM‐CBTE method for G II of dissimilar materials adhesively bonded samples was proposed. The differences in material, geometry, and clamp correction were all considered. Good feasibility of the DM‐CBTE method for evaluation of G II was validated. Abstract :